Defining conceptual boundaries of moral injury and post-traumatic stress disorder in military population: A systematic review - Zasiekina, Larysa; Kokun, Oleg; Hlova, Iryna; Bojko, Martha (East European Journal of Psycholinguistics, 2023)
Moral injury is one of the main emotional distress in military personnel. Findings suggest that in wartime there are an endless number of potentially morally injurious events, which determine maladaptive cognitions, moral emotions of guilt and shame, and inefficient behaviour. Notwithstanding the strong association between moral injury and post-traumatic stress disorder (PTSD) recognized in the number of studies, there is still a gap of accurate data aligned with identifying the differences between moral injury and PTSD in terms of treatment and healing. This study aims to establish conceptual boundaries of moral injury, post-traumatic stress disorder and systematically review the empirical literature on them in military personnel. Specifically, we explored and summarized co-occurrence of moral injury and PTSD in military personnel and evaluated the association between moral injury and PTSD, as well with other emotional distress. An intensive bibliography search screening, extraction and report focusing in moral injury and PTSD was conducted following the PRISMA recommendations. The results indicate that the key aspects of comparison of moral injury and PTSD include definition and symptomology, measurement, neural underpinning, and treatment. Considering the consequences of poor social well-being, emotional sufferings and inefficient behavioral patterns, treatments focusing on moral injury separately from PTSD-focused models are much needed. Acknowledgements This study is a part of the Moral Injury and Healing of Combatants: Neuropsychological Correlates and Psychological Interventions project funded by the Ministry of Education and Science of Ukraine (2022-2023). Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Larysa Zasiekina, 0000-0001-8456-0774 zasyekina.larisa@vnu.edu.ua